2022
DOI: 10.1101/2022.10.19.512668
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Trellis Single-Cell Screening Reveals Stromal Regulation of Patient-Derived Organoid Drug Responses

Abstract: Patient-derived organoids (PDOs) model personalized cancer therapy responses. How-ever, existing bulk PDO screening technologies cannot reveal drug response mechanisms or model how cells of the tumor microenvironment alter therapy performance. To address this, we developed a highly-multiplexed thiol-reactive organoid barcodingin situ(TOBis) mass cytometry platform to perform single-cell post translational modification (PTM) signaling analysis of colorectal cancer (CRC) PDOs and cancer-associated fibroblasts (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…This sample preparation workflow is similar to standard intra-cellular flow and mass cytometry assays [10, 11]. To minimise non-specific background staining, permeabilised cells are blocked with BSA, dextran sulphate [4], and sheared salmon sperm DNA [5], and then stained with poly-A barcoded oligonucleotide-tagged antibodies targeting cytoplasmic and nuclear PTMs and intra- and extra-cellular proteins (previously validated using mass cytometry [10, 11, 12, 13]).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This sample preparation workflow is similar to standard intra-cellular flow and mass cytometry assays [10, 11]. To minimise non-specific background staining, permeabilised cells are blocked with BSA, dextran sulphate [4], and sheared salmon sperm DNA [5], and then stained with poly-A barcoded oligonucleotide-tagged antibodies targeting cytoplasmic and nuclear PTMs and intra- and extra-cellular proteins (previously validated using mass cytometry [10, 11, 12, 13]).…”
Section: Resultsmentioning
confidence: 99%
“…Deregulated PTM signalling can then alter cancer cell gene expression to drive phenotypic plasticity [20]. For example, in colorectal cancer (CRC) inter-cellular signalling from cancer associated fibroblasts (CAFs) can regulate cancer cell PTM signalling to polarise cancer cells from a chemosensitive proliferative colonic stem cell (proCSC) fate to a chemorefractory revival stem cell (revCSC) fate [12, 21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results confirmed that TGF-β can induce revCSC-like cells in CRC organoids, but this process is rare (Figure S3C) and requires low PI3K signalling (Figure 5F). Moreover, we recently demonstrated that cancer associated fibroblasts (CAFs) can also induce a revCSC-like state in CRC patient-derived organoids (PDOs) that protects CRC cells from chemotherapies including fluorouracil, oxaliplatin, and irinotecan [38]. In this model, CAF-chemoprotection can also be overcome by inhibiting YAP signalling – further demonstrating the central role of YAP in revCSC identity.…”
Section: Discussionmentioning
confidence: 99%
“…Chris Tape from the UCL Cancer Institute gave a talk on single‐cell analysis of drug response mechanisms inpatient‐derived organoids (PDOs) and cancer‐associated fibroblasts (CAFs), showing that CAFs alter PDO drug sensitivity by cell‐fate plasticity switching and mechanistic insights can drive rational drug re‐sensitisation [31]. Chris particularly emphasised that cell‐extrinsic cues can regulate cancer cell dependencies and that future DepMap efforts would benefit from incorporating elements of the tumour microenvironment.…”
Section: The 1st Eurodepmap In Numbersmentioning
confidence: 99%